SARC‐F Questionnaire: Rapid and Easy Tool for Identifying Physical Limitations in Hemodialysis Patients. Issue 1 (1st January 2019) - Yamamoto, Shohei; Matsuzawa, Ryota; Harada, Manae; Watanabe, Takaaki; Shimoda, Takahiro; Suzuki, Yuta; Kamiya, Kentaro; Osada, Shiwori; Yoshida, Atsushi; Matsunaga, Atsuhiko
Abstract: Background: SARC‐F is a simple questionnaire for rapidly assessing physical function and screening for sarcopenia. This study aimed to determine whether the SARC‐F questionnaire is useful for identifying impaired physical function and the risk of physical limitations in hemodialysis patients. Methods and results: This cross‐sectional study included 281 patients undergoing hemodialysis at two dialysis units. SARC‐F, handgrip strength, leg strength, one‐leg standing time, usual gait speed, and short physical performance battery (SPPB) score were measured. Patients were classified according to the SARC‐F score (SARC‐F <4 and SARC‐F ≥4), indicating the risk of sarcopenia. Furthermore, we defined physical limitations as handgrip strength of <26 kg for men and <18 kg for women, leg strength of <40%, usual gait speed of ≤0.8 m/s, and SPPB score of ≤8 points. To calculate the areas under the curves (AUCs) of the SARC‐F score for physical limitations, receiver‐operating characteristic curve analysis was performed. SARC‐F ≥4 was observed in 75 (26.7 %) hemodialysis patients. The SARC‐F ≥4 group had a significantly lower handgrip and leg strength, shorter one‐leg standing time, slower usual gait speed, and lower SPPB score than the SARC‐F <4 group, even after adjusting for potential confounders (all P <0.001). Further, SARC‐F demonstrated good accuracy in identifying the risk of physical limitations (all AUCs > 0.75). Conclusions: The SARC‐F questionnaire is useful for screening impaired physical function and for identifying the risk of physical limitations in hemodialysis patients and can be easily and rapidly administered to this patient group in clinical practice.